Medicinal plants used by traditional medicine practitioners in treatment of alcohol-related disorders in Bushenyi District, southwestern Uganda - Maling, Samuel; Kabakyenga, Jerome; Muchunguzi, Charles; Olet, Eunice Apio; Namaganda, Mary; Kahwa, Ivan; Alele, Paul Erasmus (Frontiers in Pharmacology, 2024)
Background Alcohol-related disorders rank seventh among risk factors for morbidity and mortality globally, posing a significant public health burden. In Africa, including Uganda, there is limited availability and utilization of pharmacotherapies to treat alcohol-related disorders. This study documented medicinal plant species, plant parts used, and the methods of preparation and administration utilized by Traditional Medicine Practitioners (TMPs) in treating alcohol-related disorders in southwestern Uganda. Methods A descriptive cross-sectional ethnopharmacological survey was conducted among TMPs within Bushenyi District, southwestern Uganda. Data was collected with key informant interviews using semi-structured questionnaires. The TMPs identified medicinal plants by local names. Plant specimens were collected and deposited at the Department of Biology, Faculty of Science, Mbarara University for identification and voucher numbers allocated. The plant scientific names and species were identified based on the International Plant Names Index. Plant species, family, life form, number of mentions, method of collection, preparation and administration were analyzed using descriptive statistics in Microsoft Excel. The survey data were utilized to compute Frequency of Citation, Relative Frequency of Citation, and Informant Consensus Factor. Results We enrolled 50 traditional medicine practitioners aged between 34 and 98 years, with a mean age of 67. Approximately two-thirds were female (66%, 33/50), and mean experience in traditional healing was 31 years. The total number of plants identified were 25 belonging to 20 families. The most prevalent plant life form was herbs (36%) while grasses (4%), were the least. Leaves (48%) were the most utilized plant parts with the least utilized being the barks. The most prevalent method, adopted by approximately one-third of the TMPs, involved drying the plant material in the sun. The Informant Consensus Factor was 0.67. Conclusion The study shows that the traditional medicine practitioners in Bushenyi district use a wide diversity of plants species to treat alcohol related disorders. The relatively high Informant Consensus Factor suggests a significant level of agreement among TMPs regarding the use of the identified plants. We recommend further investigations into phytochemistry, safety, efficacy, and mechanisms of action of the identified plants.